Free dynamics and quantum Zeno effect of qubit coupled to a single mode field in dissipation environment. (24th February 2017) - Wu, Shan; Li, Haichao; Zhang, Jiying; Su, Chong; Fu, Cheng
Abstract: We investigate the long time evolution of a qubit coupled to an intrinsic bath and a single mode field which is coupled with a cavity bath, with and without repetitive measurements. We also analyze the measurement-modified decay rate, which shows that the free decay rate does not necessarily exist in some systems. The free decay rate is widely used to distinguish the quantum Zeno effect and anti-Zeno effect (AZE). It indicates that one cannot always make that clear if a decay of a system is accelerated. Our model confirms this conclusion; it shows that the AZE is not a universal concept.